KORUPSI SEBAGAI EXTRA ORDINARY CRIMES - Sigit Herman Binaji; Hartanti Hartanti (Kajian Hukum, 2019)
Corruption is a foul act, like being bribed. It has damaged not only the legal finances and legal economic potential, but also the socio-cultural, moral, political and legal pillars of the national security and law. Corruption is an extraordinary crime (Extra Ordinary Crimes) because it is done by people who have positions or power, which is carried out systematically, structured, and neatly cooperated with the others to cover up their actions, with the aim of getting money, goods or something for personal and family interests. The impact caused by corruption assuredly endangers the community. Factors causing corruption are very complex, including those related to lifestyles (consumptive), integrity/ morality/ mental attitude, attitude/ behavior, legal environment culture, economic needs/ demands, opportunities, and economic legal gaps which lead to jealousy of the law, the vulnerability of the bureaucracy,surveillance systems,and legal services. The causes of corruption are apparently very broad/ multi-dimensional. Corruption prevention efforts are conducted by making better changes in all areas of life both personally and institutionally. They are done by involvingcommunity participations, one of which is to report to the authorities when they know or even experience a criminal act of corruption (being whistleblower) and cooperate with the law enforcement in exposing corruption(being justice collaborator). Besides, ratifying the conventions related to eradication of corruption and issuing various regulations are needed to be done in order to prevent the occurrence of criminal acts of corruption.Keywords: Corruption, causes, prevention